The preventive effect of aqueous extract of Rosemary (Rosmarinus officinalis) leaves against the nephrotoxicity of carbon tetrachloride in mice. (26th May 2020) - Hamed, Houda; Boulila, Salha; Ghrab, Ferdaws; Kallel, Rim; Boudawara, Tahia; El Feki, Abdelfattah
Abstract: The present study aimed to evaluate the performance effect of aqueous extract of Rosmarinus officinalis (AERO) against the kidney toxicity induced by CCl4 in mice. The results showed that the renal damage induced by CCl4 was associated with a rise in oxidative stress monitored by a significant increase of TBARS and PCO levels (+89% and +136% respectively, p  < .001) and a significant decrease of GSH level (–68%, p  < .001) and antioxidants enzymes such as SOD, CAT, and GPX activities (–41.7%, –47.8%, and –50.5%; p  < .001, respectively). Also, the nephropathology parameters including creatinine, BUN, and urea (+68.9%, +47%, +48·6% respectively, p  < .05) were remarkably increased. These findings were substantiated by histological study. Pretreatment with Rosemary extract significantly attenuated the CCl4 related toxic effects via more than one mechanism such as the inhibition of lipid peroxidation, the stimulation of the synthesis of cellular antioxidants, the decrease of the biomarker kidney and the correction of the kidney structure. We can conclude that the Rosemary is efficient in the prevention of kidney function against CCl4 toxicity.